ARGUMENTASI, SOLUSI, DAMPAK EKONOMI DAN PERILAKU HARGA BBM DI INDONESIA - Fatihudin, Didin (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2013)
Fuel oil is a fundamental requirement activities and services. The fluctuations in fuel price has a major impact on economic activities. Starting from raw material to the end user, government needs to intervene oil price. The fuel shortage can be examined from three prospective. There are: producer behaviourmarket behaviour and also consumer behaviour. It could be the scarcity due to low technological innovation and exploration, is the raw material runs out or no accumulation. Fluctuations in price of fuel has a positive side and a negative side for a economic activities